An Assessment Study on the Current Use of the 4-K Club Activities in Teaching of the Competency-Based Agriculture Subject in Grades 4-6 at Primary Schools in Makindu Sub-County, Kenya. - Ndambuki , Robert Kyalo; Kyule , Miriam Nthenya; Konyango , Jacob (Journal of Education and Practice, 2024)
Purpose: This study sought to assess the current use of the 4-K Club activities in teaching of competency-based agriculture subject in grades 4-6 at primary schools in Makindu Sub-County, Kenya. Methodology: A descriptive survey research design was employed in the study. The target population of this study comprised of 926 teachers assigned to teach in grades 4-6 at primary schools in Makindu Sub-Count in Kenya. The accessible population for the study comprised of 32 teachers assigned to teach agriculture subject in grades 4-6 in the 16 schools with active 4-K Clubs in Makindu Sub-County. The census method was used to select all 32 agriculture teachers from schools with active 4-K Clubs to participate in the study. Structured questionnaires were used to collect data from the respondents. Quantitative data was analyzed descriptively using statistics such as percentages and frequencies. Data was coded and analyzed using the Statistical Package for Social Sciences (SPSS v28.0). Results were then presented in tables. Findings: The results indicated that there is little use of most of the 4-K Club activities conducted within the school farm, community and through use of ICT facilities in teaching of the competency-based agriculture subject in grades 4-6 by the agriculture teachers. However, the 4-K Club activity that was conducted at least frequently by most teachers when teaching was only guiding learners to carry out projects on crop production. Contribution to Theory, Policy and Practice: The study recommended that the teachers assigned to teach agriculture subject at upper primary to increase use of the 4-K Club activities within the school farm, community and through use of the ICT facilities in teaching of the agriculture subject. In-service training to be conducted to train primary school teachers on use of the 4-K Clubs in teaching of the agriculture subject. Government of Kenya to lay down strategies needed to keep the 4-K Clubs active in schools for current use in teaching of the competency based agriculture subject.